1967
DOI: 10.1039/tf9676302051
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of dehydroxylation of crocidolite

Abstract: The kinetics of dehydroxylation of crocidolite have been studied in Z)CICUO. The kinetic data may be interpreted in terms of a diffusion-controlled reaction based on radial diffusion out of a cylinder. The activation energy for the process is 49 kcal/mole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…1. Similar curves were observed by Clark and Freeman (1967) who studied the thermal decomposition of crocidolite, an Fe-bearing amphibole known as blue asbestos. Figure 2 shows the fraction of tremolite reacted plotted versus time normalized to the time required for 50% decomposition of the tremolite (i.e., t/t 0.5 ).…”
Section: Tremolite Decomposition Experimentssupporting
confidence: 73%
“…1. Similar curves were observed by Clark and Freeman (1967) who studied the thermal decomposition of crocidolite, an Fe-bearing amphibole known as blue asbestos. Figure 2 shows the fraction of tremolite reacted plotted versus time normalized to the time required for 50% decomposition of the tremolite (i.e., t/t 0.5 ).…”
Section: Tremolite Decomposition Experimentssupporting
confidence: 73%
“…Hence, the following diffusion controlled models (Clark andFreeman 1967 andBrindley andLemaitre 1987) were considered for analysis: One-dimensional diffusion:…”
Section: Dehydroxylation Kinetics Mechanismmentioning
confidence: 99%
“…A particularly important issue in the crystal chemistry of these minerals is the stability of Fe-bearing species, because their oxidation processes have a paramount importance in a wide spectrum of fields, including geology and geophysics, but also materials science and toxicology 6,7 . Early ex situ work 8,9 have revealed that oxidation of C Fe is intrinsically coupled with a loss of hydrogen from the hydroxyl group, in the presence of external oxygen ( ex O 2 ), according to the reaction:…”
mentioning
confidence: 99%